The Equilibrium Value of the Euro/ US Exchange Rate: An Evaluation of Research - Jerome L. Stein (Center for Economic Studies and ifo Institute (CESifo), 2001)
The ultimate object of research concerning the Euro is to answer the following questions: (#1) What is the equilibrium trajectory of the nominal euro, measured as dollars/euro? (#2) To what extent has the equilibrium nominal euro been determined by relative prices (PPP), and to what extent has it been determined by real fundamentals? (#3) How important have been the transitory factors in affecting the value of the euro? (#4) Is the euro currently undervalued, and by what criteria? Our evaluation of recent research concerning the answers to these questions, is the subject of this paper.
Keywords: 330; Euro; NATREX; BEER; equilibrium exchange rates; international capital flows; misalignment